Contribution at epidemiologic study ofcongenital syphilis in Carapicuíba-SP City: still a reality in 2002 - Vieira, Amadeu A. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction:this study is about congenital syphilis. syphilis and congenital syphilis declined rapidly after the introduction of penicillin therapy, keepinglow levels, but in the end of 1960`s and the beginning of 1970`s there was a dramatic increase in syphilis and Congenital Syphilis cases caused by lackof prevention and inadequate antenatal care, multiple sexual partners, people marginalised by chemical dependency and illicit drug use, poverty, prostitu-tion and associated with human immunodeficiency (HIV). Objective: describe the cases of congenital syphilis of residents in the town of Carapicuíba,São Paulo.. Methods:retrospective study about prevalence of Congenital Syphilis cases from infants borned on Carapicuíba city in 2002; the cases werenotifiable for the statistics system (Sistema de Informações de Agravos de Notificação – SINAN-WIN) from the local health authority. Results:the pre-valence of Congenital Syphilis was 0,48% (32 notifiable cases in 6.719 births) that means a rate of 4,76 cases per 1.000 live births; 31 cases were classifi-cated like presumptive Congenital Syphilis and only one was confirmed. All of the cases were termed early Congenital Syphilis. Conclusion: the rate ofCarapicuíba city was higher than one case per 1.000 live births as Pan American Health Organization (PAHO) and the Ministry of Health in Brazil (MH)wants to, but its rate is 33,9% lower than the research made by the Congenital Syphilis Group Investigation of Ministry of Health in Brazil. This studyshows how important is the rate of Congenital Syphilis to indicate the Public Health Department quality, in particular the antenatal and neonatal care.Despite Congenital Syphilis being a notifiable disease, health personnel remain unaware it. If this disease is to be controlled and the purposes of notifica-tion met, heigtened awareness and education of both the public and the health care provides is essential.